HUBUNGAN ANTARA PERILAKU MEROKOK DENGAN KEJADIAN SINDROM MATA KERING PADA MASYARAKAT KELURAHAN OESAPA KOTA KUPANG - Songkares, Adelaida Olga Malobo; Hutasoit, Regina Marvin; Rante, Su Djie To; Manafe, Derri R. Tallo (Jurnal Kesehatan Masyarakat, 2023)
Cigarette smoke can damage the lipid layer and cause tear hyperosmolarity that may lead to dry eye syndrome symptoms. This study aim to determine the relationship between smoking behavior and dry eye syndrome in the community of Oesapa Ward, Kupang City. This research is an observational analytic study with a cross sectional design. Data was conducted by filling out the Smoking Behavior questionnaire and Ocular Surface Disease Index (OSDI) questionnaire. Sampling was done by using stratified random sampling technique and the result was analyzed univariate and bivariate using Spearman Rank correlation test. Data from the 110 respondents, 96.4% had high smoking behavior, 3.6% had moderate smoking behavior and none had low smoking behavior. For dry eye, 49.1% had normal eyes, 21.8% had severe dry eyes, 19.1% had mild dry eye syndrome and 10.0% had moderate dry eye syndrome. The bivariate analysis with the Spearman Rank correlation test showed the results of p = 0.952 (p>0.05). The conclusion is there is no significant relationship between smoking behavior and dry eye syndrome in the community of Oesapa Ward, Kupang City.